2009
DOI: 10.1007/s11581-009-0364-y
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and electrochemical performances of carbon-coated TiO2 anatase

Abstract: Several carbon-coated anatase TiO 2 samples have been prepared by impregnation with lactose as carbon precursor and annealed at different temperatures (650 and 700°C). X-ray diffraction was carried out to study the anatase to rutile phase transition and to evaluate the crystallite size. Scanning electron microscopy was utilized to evaluate the morphology, and transmission electron microscopy was used to show the distribution and nature of the carbon coating. The galvanostatic measurements and cyclic voltammetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The final particle size for the carbon coated titania was 10 nm. It has been generally observed that coating of small crystallites by a second phase inhibits growth of the crystallites during annealing process (22,28). However, in the present case, the TiO 2 nanoparticles are in agglomeration with broad pore size distribution (see the Supporting Information, Figure 2b) prior to carbon treatment.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The final particle size for the carbon coated titania was 10 nm. It has been generally observed that coating of small crystallites by a second phase inhibits growth of the crystallites during annealing process (22,28). However, in the present case, the TiO 2 nanoparticles are in agglomeration with broad pore size distribution (see the Supporting Information, Figure 2b) prior to carbon treatment.…”
Section: Resultsmentioning
confidence: 60%
“…The formation of bigger crystallites in case of T400 and TC400 is attributed to temperature induced crystallization. It must be mentioned here that the annealing temperature of 400 °C was selected to prevent phase transitions from anatase to rutile (28).…”
Section: Resultsmentioning
confidence: 99%
“…However, the preparation of a pure anatase sample with an efficient carbon coating could not be implemented satisfactorily. 185 Another approach has been studied by Ishii et al 186 by introducing a triblock copolymer (Pluronic F127 (PEO 106 PPO 70 -PEO 106 )) during the precipitation step and using it as a carbon source. In this case no rutile formation has been observed and the composite maintained a high reversible capacity of 109 mAh g -1 even at high current densities of 1000 mA g -1 .…”
Section: Carbon Coatingmentioning
confidence: 99%
“…24 To solve this problem, one common approach is to modify the surface of electrodes with transition metal ions, transition metals, transition metal oxides and so on. Many methods have been used to accomplish this, such as directly mixing followed by calcination, 25 physical vapor deposition (PVD) 26 and atomic layer deposition (ALD). 27 However, these methods require complicated procedures and induce high cost; in addition, it is still not easy to obtain homogeneously modified nanostructures.…”
Section: Introductionmentioning
confidence: 99%